Face Recognition Using PCA Technique - Agrawal, Divesh N; Kapgate, Deepak (International Journal of Computer Sciences and Engineering, 2014)
This paper provides the information about Face Recognition Technology which gives the much more security in the field of multimedia and information technology. To provide the protection to the data we keep the password but as we know hackers can break the password, for that we keep password as our face. Thus for accessing some network or PC by an unauthorized person is virtually impossible and it helps to protect our data. It also provides the user friendliness in human interaction with computer as there is no such physical touch. In this image is captured and stored into database in compress form. Its benefits show in retrieval and in matching. Like the applications of teleconferencing and video call, face recognition is more efficient. Most of the cameras have this application of face recognition which detects the human face and shows appropriate square box on face. In this paper there is an introductory part of this technology. This shows the generic framework and variants that are frequently use by the face recognizer. Some well known face recognition algorithms, such as PCA, Eigenfaces, will also be explained in this paper.